História e histórias entrelaçadas pela voz: a narrativa performática em O Alegre Canto da Perdiz, de Paulina Chiziane - Santos, Márcia Cristina dos (2010)
The aim of this dissertation is to think about the hybrid writing of the African novel The Happy Partridge s Song (2008) of the authorship of Paulina Chiziane. The research of this reading of the Mozambican novel pointed out in the orality, boundaries and narrative performance, consequent of the intersection between voice and letter, in agreement with the mythical origins of its culture. The items of the our research are inter-related with the figurative sights of the questions between relation tradition and modernity and their insurgencies in the social reality of Zambezia, especially, in relation to black woman while loud voice looking for autonomy, social status and individual freedom. The light of this culture social question, bring us as a result that change and the emptying of social positions occupied by woman in troubles bring up a eccentric writing by the communicated dialogism of the word with the orality, responsible method by the fusion of two or more voices in the representation of hybrid speech of the novel. The effect is the constant and invariable mobility of the narrator and her ideological eminence in the handling passionate and libertarian trouble of the black woman voice in the context of the patriarchal society, like voices linked authorial